Lingkungan Pendidikan Islam dalam Membentuk Insan Kamil - Alfin Maskur (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
Islamic education serves as the fundamental foundation in shaping the character and morals of individuals, especially children undergoing the crucial stages of growth and development. The Islamic educational environment, as a vital component, plays a pivotal role in determining the success of the learning process. Despite social interaction being part of the environment, it does not always result in education, even though there are potential factors that could contribute to the educational process. Therefore, this research explores the urgency, argumentation, and significance of the Islamic educational environment to understand how these factors can be optimized to achieve holistic Islamic educational goals. The importance of Islamic education extends beyond religious knowledge, encompassing the formation of attitudes, morals, and religious feelings in children. The environment, as the space for interaction between individuals and surrounding factors, significantly influences the development of a child's soul, both positively and negatively. This article delves deeply into the role of the Islamic educational environment, how environmental factors shape a child's character, and the importance of a profound understanding of the concept of the Islamic educational environment to achieve optimal learning goals.